2002
DOI: 10.1007/s00253-002-0966-z
|View full text |Cite
|
Sign up to set email alerts
|

Process technological effects of deletion and amplification of hydrophobins I and II in transformants of Trichoderma reesei

Abstract: Transformants of the Trichoderma reeseistrains QM9414 and Rut-C30 were constructed in which the genes for the two major hydrophobin proteins, hydrophobins I (HFBI) and II (HFBII), were deleted or amplified by molecular biological techniques. Growth parameters and foam production of the transformant strains were compared with the corresponding properties of the parent strains by cultivation in laboratory bioreactors under conditions of catabolite repression (glucose medium) or induction of cellulolytic enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although hydrophobins are not known to have a major influence in cellulase efficiency [54], deletion of the strongly regulated NCU08192 (related to the M. grisea hydrophobin MHP1 [55], cluster 4), that showed increased expression levels in both white collar mutants, unexpectedly had significantly increased specific cellulase activity (Figure 7). A strain containing a mutation in another hydrophobin-like protein belonging to cluster 2 ( ccg-14 /NCU07787), encoding a ceratoplatanin-like small protein [56,57] displayed cellulolytic activity indistinguishable from WT (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Although hydrophobins are not known to have a major influence in cellulase efficiency [54], deletion of the strongly regulated NCU08192 (related to the M. grisea hydrophobin MHP1 [55], cluster 4), that showed increased expression levels in both white collar mutants, unexpectedly had significantly increased specific cellulase activity (Figure 7). A strain containing a mutation in another hydrophobin-like protein belonging to cluster 2 ( ccg-14 /NCU07787), encoding a ceratoplatanin-like small protein [56,57] displayed cellulolytic activity indistinguishable from WT (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…HFBs are also involved in symbiotic interactions, such as those between lichens and mycorrhizae [ 24 , 25 ]. HFBs play a role in development and morphogenesis in the majority of the filamentous fungi and influence spore properties (for reviews, see [ 26 29 ]). Thus, we hypothesized that the respective genes could be suitable targets for ecological genetic investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Study suggested that deletion of hydrophobin genes from fungal species lead to minimal foaming during fermentation process. Genes of HFBI and HFBII deleted from T. reesei resulted in developing less foam during fermentation process due to absence of these proteins in fermentation broth in comparison to wild type strain [44].…”
Section: Foam Production and Stabilitymentioning
confidence: 99%